Ilovnate zapolnitve v udornicah v zaledju izvirov Ljubljanice - Stepišnik, Uroš (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2006)
The article discusses formation and transformation processes of collapse dolines in the hinterland of Ljubljanica river springs near Vrhnika. The characteristics and mechanisms of flat loamy sediment floors in collapse dolines have been studied in detail. Loamy sediment fills in the collapse dolines are the result of suspended material sedimentation from floodwaters that inundated lower parts of collapse dolines. The method of ground electrical resistance established that the thickness of loamy sediment fills might reach more than 30 meters.
Keywords: kraške jame; List of caves in Slovenia; udori; sedimenti; kraška ilovica; Ljubljanica; Vrhnika